Incidence of the pink hibiscus mealybug in mango cultivars from Nayarit, Mexico - Rosas-García, Ninfa M.; Parra-Bracamonte, Gaspar M. (Instituto de Ecología, A.C., 2011)
The incidence of the pink hibiscus mealybug (PHM) Maconellicoccus hirsutus (Green) (Hemiptera: Pseudococcidae) was evaluated in six cultivars of mango grown in Bahía de Banderas state of Nayarit, México. The incidence of the pest was determined by monitoring each developmental stage, first instar nymphs or crawlers (N1), second instar nymphs (N2), third instar nymphs (N3), females (F), and ovisacs (O) on Tommy Atkins, Haden, Manila, Ataulfo, Keitt, and Kent cul-tivars. Presence of insects was also determined in three different locations: terminal buds and fruits in trees, as well as surrounding weeds. Results indicated that average monthly incidence of N1 and N2 individuals was higher between January and February, May and June, and August and September, incidence of N3 individuals was also higher between July and August. All developmental stages showed the highest incidence in cultivar Ataulfo. Mean number of N1 and N2 individuals on fruits and weeds did not show significant difference, but mean number of N3 individuals, females and ovisacs on fruits was higher with respect to individuals on buds and weeds. Results suggest an interaction among the developmental stages, cultivars and tree phenology. A preference of the first instars for cultivar Ataulfo was observed, as well as a preference of N3 individuals for fruits. It is important to assess the susceptibility of mango cultivars to PHM attack in order to perform a suitable control to avoid pest dissemination.